Difficulties in Teaching Biology Curricula in Secondary Education from the Perspective of Teachers in the City of Nalut, Libya - Batar, Hotaf; Afleefil, Asmaa (Sharwes Scientific Journal, 2025)
The research aimed to identify the difficulties facing teachers in teaching biology in secondaryschools in Nalut city, Libya, from their point of view. The descriptive analytical approach wasused, including a questionnaire tool prepared to achieve the research objectives. Thequestionnaire focused on 6 axes derived from previous studies. The research communityconsisted of all biology teachers in the city and (21) teachers responded to represent the researchsample. After conducting statistical analyses, the research results showed that (3) axes obtainedan average response degree, arranged in descending order as follows: the axis of difficultiesrelated to the curriculum, then the axis of difficulties related to the student, followed bydifficulties related to educational tools. As for the remaining axes, they obtained a low responsedegree, and they are as follows: the axis of difficulties related to teaching methods, followedby the axis of difficulties related to assessment, and finally those related to the teacher. Themost prominent findings of the research are that teachers face difficulties in teaching biologyin secondary schools in Nalut, the most important of which are: the lack of training coursestargeting teachers, students memorizing biology without understanding it, parents not followingup with their children in school, the lack of requirements for applying modern teaching methodsfor biology, the large content of the textbook and its unsuitability for the time allocated to it,the lack of biology laboratories and if they are available, they are not equipped in a way thatmeets the needs of the subject.